Development and validation of the Penn Arthralgia Aging Scale among breast cancer survivors. Issue 16 (29th April 2015) - Brier, Moriah J.; Chambless, Dianne L.; Lee, Laura; Mao, Jun J.
<x xml:space="preserve">Abstract</x> BACKGROUND Breast cancer survivors on aromatase inhibitors often experience joint pain as a side effect of their treatment; qualitative investigations suggest that this arthralgia may cause women to feel that they are aging faster than they should be. To facilitate further study of this experience, the Penn Arthralgia Aging Scale (PAAS) was developed. This report describes the development and validation of the PAAS in a racially diverse sample of breast cancer survivors suffering from joint pain. METHODS The items of the scale were developed from a content analysis of interviews with patients. The scale was pilot‐tested, and modifications were made on the basis of patient feedback. Subsequently, 596 breast cancer survivors who endorsed joint pain completed the 8‐item PAAS. The factor structure (with exploratory factor analysis), the internal consistency, and the convergent, divergent, and incremental validity were examined. RESULTS The resulting scale had a 1‐factor structure with strong internal consistency (Cronbach's α = .94) and demonstrated both convergent and divergent validity: the PAAS was significantly correlated with joint pain severity (rs = 0.55, P < .01) and had a small and nonsignificant correlation with actual age (rs = –0.07, P = .10). The PAAS was also found to explain incremental variance in anxiety, depression, and pain interference outcomes. CONCLUSIONS These findings suggest that the PAAS produces reliable and valid scores that capture perceptions of aging due to arthralgia among breast cancer survivors. With further research, the PAAS may advance our understanding of how perceptions of aging may affect breast cancer survivors' emotional, behavioral, and clinical outcomes. Cancer 2015;121:2808‐2813. © 2015 American Cancer Society